Using a User Centered Design Approach to Design Mindfulness Conversational Agent for Persons with Dementia and their Caregivers - Seah,CEL; Sun,S; Zhang,Z; Porat,T; Waterhouse,A; Calvo,RA (2023)
Caring for people with dementia is itself a difficult task affecting the wellbeing and relationship of the patient and carer. Conversational agents (CA), like Alexa, can support mindfulness training for these dyads of persons with early-stage dementia and their caregivers. But so far, no study has utilised a user centered design (UCD) approach for such interventions. We address this, using an iterative UCD approach where experts in dementia and mindfulness (N=4) and end-users (carers and patients, N=20) were interviewed. Four design iterations resulted in the creation of a working prototype. From this expert and user feedback, general user needs were identified and integrated into future designs. By addressing the needs of dyads, the prototype CA could be well received and may be used to support mindfulness practices using CA, that could be helpful for dyads.